PEMBELAJARAN DAN APLIKASI MAKNA INTERPERSONAL: TRANSAKSIONAL: PROPOSAL SEBAGAI PEMAHAMAN AKTIVITAS BERBAHASA STAF HOUSEKEEPING DAN FOOD AND BEVERAGE SERVICE DALAM MENGHADAPI PERMINTAAN DARI TAMU ASING (Pendekatan Linguistik Sistemik Fungsional) - Vilya Lakstian Catra Mulia (PRASASTI: Journal of Linguistics, 2015)
Hotel staffs are obligated to have skills for handling guests‟ requests, especially for housekeeping (HK) and food and beverage (FB) divisions. The services arenot only limited to which are done physically, but also in language issues. HK and FB, who are dominantly not English-educated background, have course,especially for encountering various requests from foreign guests. This article iscomposed by the writer from his experience as English instructor for those staffs.He teaches the English lesson purposed for the staffs so that they can identifythere is a request from the guest and how to respond. The learning was done byusing systemic functional linguistics approach, through modulated interrogativeand inclination clauses, to reach the goal. Both showed exchanges toward goodsand service. This learning has found a new way in language activity, so that thelearners can internalize themselves towards language structures which havecertain function with reasoned background relating to context.Key Terms Definitions: housekeeping, food and beverage, guests, hotel,requests, English, systemic functional linguistics, interrogative, inclination,modulation